Community Pharmacists’ Perspectives on Offering Discounted Prices for Prescription Drugs in Jordan - Mukattash, Ibrahim Lewis; Tahat, Tasneem Y; Ajlouny, Sara; Mukattash, Tareq L.; Al Tall, Yara; Jarab, Anan S.; Alabbadi, Ibrahim (Jordan Journal of Pharmaceutical Sciences, 2024)
Background: In Jordan, medicines are priced by the Jordan Food and Drug Administration (JFDA), which mandates pharmacists to sell pharmaceutical products without any discounts or rebates. However, discounting drug prices in community pharmacies is commonplace. The present study aims to understand the motives and perceptions of pharmacists regarding drug price discounts in community pharmacies in Jordan. Methods: Qualitative interview sessions were conducted with a convenient sample of 20 community pharmacists. A total of 25 participants were interviewed, anonymized, and audio recorded. To ensure maximum comfort, respondents were given the option to choose the interview location or participate through audio-visual communication tools. The sessions followed a pre-designed interview guide focusing on discounts offered on prescription drugs in community pharmacies, pharmacists’ experiences, and their attitudes toward these practices. Interview recordings were transcribed and analyzed thematically. Results: Three main themes emerged: patient-related factors, pharmacist-related factors, and rules and regulations-related factors, each with several subthemes. This study identified several barriers that hinder pharmacists’ adherence to medicine pricing policies in community pharmacies in Jordan, including psychosocial and economic factors, customer attraction and profit increase strategies, sales tactics, market share expansion, avoidance of medicine accumulation and expiration, and issues related to regulations and law enforcement. Conclusion: The findings demonstrate that adherence to medicine pricing policies in community pharmacies in Jordan varies depending on different factors. Pharmacists may exhibit weak adherence under specific circumstances while demonstrating stronger adherence under others. This study provides insights that could inform the revision of regulations and laws governing pharmacy practices and adherence to pricing policies.